Activation of the glucocorticoid receptor rapidly triggers calcium‐dependent serotonin release in vitro. (14th March 2021) - Paul, Nicolas; Raymond, Justine; Lumbreras, Sara; Bartsch, Dusan; Weber, Tillmann; Lau, Thorsten
Abstract: Aims: Glucocorticoids rapidly provoke serotonin (5‐HT) release in vivo. We aimed to investigate molecular mechanisms of glucocorticoid receptor (GR)‐triggered 5‐HT release. Methods: Employing 1C11 cells to model 5‐HT neurotransmission, immunofluorescence and Pearson's Correlation Coefficient were used to analyze colocalization of GR, 5‐HT, vesicle membrane protein synaptotagmin 1 and vesicle dye FM4‐64FX. FFN511 and FM4‐64FX dyes as well as calcium imaging were used to visualize vesicular 5‐HT release upon application of GR agonist dexamethasone, GR antagonist mifepristone and voltage‐gated calcium channel (VGCC) inhibitors. Results: GR, 5‐HT, synaptotagmin 1 and FM4‐64FX showed overlapping staining patterns, with Pearson's Correlation Coefficient indicating colocalization. Similarly to potassium chloride, dexamethasone caused a release of FFN511 and uptake of FM4‐64FX, indicating vesicular 5‐HT release. Mifepristone, calcium depletion and inhibition of L‐type VGCC significantly diminished dexamethasone‐induced vesicular 5‐HT release. Conclusions: In close proximity to 5‐HT releasing sites, activated GR rapidly triggers L‐type VGCC‐dependent vesicular 5‐HT release. These findings provide a better understanding of the interrelationship between glucocorticoids and 5‐HT release. Abstract : In proximity to serotonin‐containing vesicles, glucocorticoids (dexamethasone) bind to glucocorticoid receptors (1) and mediate opening of L‐type voltage‐gated calcium channels (VGCC; 2). Subsequent calcium influx (3) triggers rapid vesicular serotonin release (4). This mechanism is similar to depolarization‐induced serotonin release, which also depends on L‐type voltage‐gated calcium channels (5).